Probiotic supplementation and systemic inflammation in relapsing-remitting multiple sclerosis: A randomized, double-blind, placebo-controlled trial - Rahimlou, Mehran; Nematollahi, Shima; Husain, Durdana; Banaei-Jahromi, Nasrin; Majdinasab, Nastaran; Hosseini, Seyed Ahmad (Frontiers in Neuroscience, 2022)
Abstract Background: Multiple sclerosis (MS) is a complex inflammatory disease in which demyelination occurs in the central nervous system affecting approximately 2.5 million people worldwide. Intestinal microbiome changes play an important role in the etiology of chronic diseases. Objective: This study aimed to investigate the effect of probiotic supplementation on systemic inflammation in patients with MS. Methods: A 12-week double-blind clinical trial study was designed and seventy patients with MS were randomly divided into two groups receiving probiotics and placebo. Patients in the intervention group received two capsules containing multi-strain probiotics daily and patients in the control group received the same amount of placebo. Factors associated with systemic inflammation were assessed at the beginning and end of the study. Results: Sixty-five patients were included in the final analysis. There was no significant difference between the two groups in terms of baseline variables except for the duration of the disease (P>0.05). At the end of the study, probiotic supplementation compared to the placebo caused a significant reduction in the serum levels of CRP (-0.93± 1.62 vs. 0.05 ± 1.74, P=0.03), TNF-α ( -2.09 ± 1.88 vs. 0.48 ± 2.53, P=0.015) and IFN-γ (-13.18± 7.33 vs. -1.93± 5.99, P<0.001). Also, we found a significant increase in the FOXP3 and TGF-β levels in the intervention group (P<0.05). Conclusion: The results of our study showed that supplementation with probiotics can have beneficial effects on serum levels of some factors associated with systemic inflammation.